TECHNOFERENCE, CONFLICTS, SATISFACTION WITH COUPLE’S RELATIONSHIPS AND EMOTIONAL INTELLIGENCE CONNECTION - Dudkina, Aija; Maslinovska, Lida; Porozovs, Juris (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The purpose of the study Tehnoference, conflict, satisfaction with couple’ s relationships and emotional intelligence connection is to find out is there a relationship to technology and the frequency of conflicts in couple relationships, satisfaction with relationships and emotional intelligence. Main questions of the study: 1.Is there a connection to the technoference and the frequency of conflicts in the relationship? 2.Is the frequency of conflicts in a relationship related to satisfaction with relationships? 3.Is there a relationship to an emotional intelligence with a technofrence? 4.Is there a relationship between emotional intelligence and satisfaction with relationships?